If I say you're authentic, then you're authentic: Power and privilege revealed in travel blogs. (December 2019) - Duffy, Andrew
A leitmotif in scholarship on travel texts has been themes of power and privilege. It is not clear, however, whether the more populist, egalitarian and non-elitist form of travel media, travel blogs, fits into this pattern. This article considers the role of power in how bloggers press authenticity into service as a marker of value in travel. It argues that they use authenticity to place themselves in a position of privilege and power over the local people they interact with. It identifies three forms of traveller authenticity – experience, existence and expectation – as a framework to study structures of power, privilege and dominance implicit in travel as revealed by its use in travel blogs. These forms of authenticity all demonstrate the traveller's positioning of the self at the centre of the gaze on others. This has application for future theorising on the label of 'authenticity' as a tool of power.